2013
DOI: 10.1016/j.electacta.2013.03.132
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of heat generation in a reconstructed LiCoO2 cathode during galvanostatic discharge

Abstract: A three dimensional numerical framework with finite volume method was employed to simulate heat generation of a semi lithium ion battery (LIB) cell during isothermal galvanostatic discharge processes. The microstructure of the LIB cathode electrode was experimentally determined using X-ray nano computed tomography technology. Heat generation in the semi LIB cell during galvanostatic discharge processes from different mechanisms, such as electronic resistive heat, ionic resistive heat, contact resistive heat, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 43 publications
0
56
0
Order By: Relevance
“…As Yan et al [31] predicted, the heat density of battery under 10 C discharge rate could exceed 1,000,000 W m -3 . The composites with low paraffin ratio but high density is definite to attract considerable attention.…”
Section: Effects Of Packing Density and Paraffin Mass Fraction Of Thementioning
confidence: 98%
“…As Yan et al [31] predicted, the heat density of battery under 10 C discharge rate could exceed 1,000,000 W m -3 . The composites with low paraffin ratio but high density is definite to attract considerable attention.…”
Section: Effects Of Packing Density and Paraffin Mass Fraction Of Thementioning
confidence: 98%
“…However, detailed numerical modelling of electrode structures [26] or multi-dimensional approaches [12,14e15] require single electrode properties. Data of single electrodes or electrode coatings additionally facilitate analysis of structure-property correlations to predict thermal conductivities of electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the high surface roughness of realistic microstructure favored high instantaneous power performance but accelerated side reactions which have a negative impact on power performance. Based on X-ray nano-computed tomography (nano-CT) images, Yan et al reconstructed the electrode microstructure and developed a FVM framework to conduct 3D simulation of a half cell with LiCoO 2 cathode [15,16]. They found that the physical and electrochemical variables were distributed in a wider range than that from the pseudo 2D model due to the microstructural inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%